Dynamics of Cocoa Bean Pulp Degradation during Cocoa Bean Fermentation: Effects of Yeast Starter Culture Addition - Laras Cempaka; Lienda Aliwarga; Susanto Purwo; Made Tri Ari Penia Kresnowati (Institute for Research and Community Services (LPPM) ITB, 2014)
Fermentation is a crucial step in the post-harvest processing of cocoa beans. This process comprises mixed culture microbial activities on the cocoa bean pulp, producing metabolites that act as important precursors for cocoa flavour development. Variations in the microbial population dynamics during the fermentation process may induce changes in the overall process. Thus, the introduction of a specific microbial starter culture may improve the quality of the fermentation. This article discusses the effects ofthe addition of Saccharomyces cerevisae var. Chevalieri starter culture on cocoa bean fermentation. The dynamics in the yeast concentration, sugary pulp compounds and metabolic products were measured during fermentation. The alterations in the dynamic metabolite profile were significant, although only a slight difference was observed in the yeast population. A higher fermentation index was measured for the cocoa bean fermentation with yeast starter culture, 1.13 compared to 0.84. In conclusion, this method can potentially be applied to shorten the cocoa bean fermentation time.